Acceptability of the Translation Results of the Funktionsverbgefüge Translated by Students of the Department of German Literature, Universitas Negeri Malang - Muhammad Fadhiluddin (Universitas Negeri Malang, 2020)
This research aims to describe the results of the translation of the Funktionverbgefuge form gained from the informative text “Gute Unterhaltung” by students of the Department of German Literature, class of 2014. The type of the research is qualitative. Informative text of “Gute Unterhaltung” translated by offering B students was the source of the data of the study. The data of the study consisted of the original sentences and the translated one in the target language which contain the funktionverbgefüge form. Based on the conducted research, there are 5 FVG phrases with different forms in the ‘Gute Unterhaltung’ article consisting of 3 FVG mit Akkusativobjekt phrases and 2 FVG mit Präpositionalobjekt phrases. The result of the study shows that student can translate the FVG form lexically well. However, there are many results of translated sentences with FVG mit Akkusativobjekt contextually acceptable. Meanwhile, there are many FVG sentences with Präpositionalobjekt contextual translated by students that are less acceptable and unacceptable, but there are several also results of the textual FVG mit Prapositionalobjek translation acceptable. These mistakes occur due to misconceptions of the context, incorrect translation methods and inadequate word choice.